Development of Song Videos Based on “Sumbang Duo Baleh” to Stimulate Early Childhood Character in Learning - Hadiyanto, Hadiyanto; Mahdaleni, Mahdaleni; Delvi Eliza, Delvi Eliza; Aprilianda, Rini (Universitas Negeri Padang, 2023)
Curriculum renewal is expected to be able to respond to the challenges and competition of the 21st century by focusing on character formation which is the embodiment of national education goals. Based on initial observations and interviews conducted by researchers at Al Azhar Kindergarten in West Pasaman during the middle of 2021 to April 2022, it was found that there was a problem of lack of teacher stimulation towards children in forming attitudes and behavior such as in speaking, dressing and behaving, not being polite and courteous in playing activities. and study. The aim of this research is to develop a video for the song Sumbang Duo Baleh which can stimulate the character of young children aged 5-6 years in learning. This research and development implement ADDIE model, which includes Analysis, Design, Development, Implementation, and Evaluation. The product of this research is a video song based on Sumbang Duo Baleh which can be used to stimulate the character of young children in learning. In addition, there is an output in the form of publication of scientific articles in the accredited national journal Sinta-3. The song video based on Sumbang Duo Baleh as a learning medium has been tested for validity by 3 experts in the field, tested for practicality by teachers and tested for effectiveness in the learning process with students. From the results of the analysis that has been carried out, it can be concluded that the learning videos based on Sumbang Duo Baleh are valid, practical and effective for stimulating the character of early childhood, proven analytically and experimentally on a limited sample to stimulate the character of early childhood in the learning process.